Contemporary strategy analysis - Grant, Robert M. (Wiley, 2016)
The ninth edition of Contemporary Strategy Analysis: Text and Cases focuses on the fundamentals of value creation with an emphasis on practicality. Topics in this edition include: platform-based competition and ecosystems of related industries; the role of strategy making processes; mergers, acquisitions and alliances; and strategy implementation. Within the twenty case studies, students will find leading companies that are familiar to them. This strategy analysis text is suitable for MBA and advanced undergraduate students